2023
DOI: 10.1021/acs.est.3c06058
|View full text |Cite
|
Sign up to set email alerts
|

Direct Environmental Lead Detection by Photoluminescent Perovskite Formation with Nanogram Sensitivity

Lukas Helmbrecht,
Sjoerd W. van Dongen,
Arno van der Weijden
et al.

Abstract: Although the global ban on leaded gasoline has markedly reduced lead poisoning, many other environmental sources of lead exposure, such as paint, pipes, mines, and recycling sites remain. Existing methods to identify these sources are either costly or unreliable. We report here a new, sensitive, and inexpensive lead detection method that relies on the formation of a perovskite semiconductor. The method only requires spraying the material of interest with methylammonium bromide and observing whether photolumine… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Moreover, we showed that this perovskite-based lead test is at least 1000 times more sensitive compared to state-of-the-art rhodizonate tests under laboratory conditions. [28] Unexpectedly, despite the notoriously problematic stability of perovskites, we detected lead in objects such as paints, waterpipes, dust, glass, and plastic, demonstrating that testing in real-world environments and conditions is feasible in a robust and reliable manner.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Moreover, we showed that this perovskite-based lead test is at least 1000 times more sensitive compared to state-of-the-art rhodizonate tests under laboratory conditions. [28] Unexpectedly, despite the notoriously problematic stability of perovskites, we detected lead in objects such as paints, waterpipes, dust, glass, and plastic, demonstrating that testing in real-world environments and conditions is feasible in a robust and reliable manner.…”
Section: Introductionmentioning
confidence: 72%
“…We recently exploited the versatile chemistry of lead and the bright photoluminescence (PL) of lead halide perovskites to develop a lead testing method based on perovskite formation. [28][29][30][31] In short, direct application of a reagent containing perovskite precursors (e.g. methylammonium halides) readily reacts with lead to form a lead halide perovskite semiconductor.…”
Section: Introductionmentioning
confidence: 99%
“…The present study evaluates a new kit marketed by the Dutch start-up Lumetallix that sprung out of research on the properties of Pb-halide perovskite to improve solar panels (Stranks and Snaith, 2015). The method was optimized for visual detection to produce an intense green fluorescence using methylammonium bromide (CH 3 NH 3 Br) in isopropanol in the presence of Pb regardless of its oxidation state (Helmbrecht et al, 2023). The Lumetallix reagent directly converts Pb into a light-emitting perovskite in a wide selection of specimens ranging from plastics and paints, to glazing and glass.…”
mentioning
confidence: 99%